218k views
0 votes
Solve (2x – 1)2 = 9.

Question 19 options:

A)

x = –2, 1

B)

x = 2, 1

C)

x = 2, –1

D)

x = –2, –1

2 Answers

5 votes
Take the square root of each side of the equation to set up the solution for
x
x
(
2
x

1
)
2

1
2
=
±

9
(
2
x
-
1
)
2

1
2
=
±
9
Remove the perfect root factor
2
x

1
2
x
-
1
under the radical to solve for
x
x
.
2
x

1
=
±

9
2
x
-
1
=
±
9
Simplify the right side of the equation.
Tap for more steps...
2
x

1
=
±
3
2
x
-
1
=
±
3
The complete solution is the result of both the positive and negative portions of the solution.
Tap for more steps...
x
=
2
,

1
User Arikabc
by
6.4k points
1 vote
C because you would need to simplify the xy to the equation :)
User Srakyi
by
5.3k points